The involvement of a Nanog, Klf4 and c-Myc transcriptional circuitry in the intertwining between neoplastic progression and reprogramming - Marzi, Ilaria (Landes Bioscience, 2013)
One undisputed milestone of traditional oncology is neoplastic progression, which consists of a progressive selection of dedifferentiated cells driven by a chance sequence of genetic mutations. Recently it has been demonstrated that the overexpression of well-defined transcription factors reprograms somatic cells to the pluripotent stem status. The demonstration raises crucial questions as to whether and to what extent this reprogramming contributes to tumorigenesis, and whether the epigenetic changes involved in it are reversible. Here, we show for the first time that a tumor produced in vivo by a chemical carcinogen is the product of the interaction between neoplastic progression and reprogramming. The experimental model employed the prototype of ascites tumors, the Yoshida AH130 hepatoma and other neoplasias, including human melanoma. AH130 hepatoma was started in the liver by the carcinogen o-aminoazotoluene. This compound binds to and abolishes the p53 protein, producing a genomic instability that promotes both the neoplastic progression and the hepatoma reprogramming. Eventually this tumor contained 100% CD133(+) elements and pO(2)-dependent percentages of the three embryonic transcription factors Nanog, Klf4 and c-Myc. Once transferred into aerobic cultures, the minor cellular fraction expressing this triad generates various types of adherent cells, which are progressively substituted by non-tumorigenic elements committed to fibromuscular, neuronal and glial differentiation. This reprogramming appears to be accomplished stepwise, with the assembly of the triad into a sophisticated transcriptional, oxygen-dependent circuitry, in which Nanog and Klf4 antagonistically regulate c-Myc, and hence, cell hypoxia survival and cell cycle activation.